ISCHEMIC INJURY OF KIDNEY ALLOGRAFTS AND EXPRESSION OF MATRIX METALLOPROTEINASES - M. L. Arefjev; M. G. Minina; I. M. Iljinsky (Вестник трансплантологии и искусственных органов)
In the following paper we present the literature review concerning the correlation between the ischemic injury of kidney allografts and matrix metalloproteinases activity.